PENDHAPA SASANA SEWAKA KERATON KASUNANAN DI SURAKARTA Mitologi dan makna simbolis - Santoso Haryono (Gelar : Jurnal Seni Budaya, 2010)
Sasana Sewaka is a name of the main building of the court in the form of joglo. The building with a Javanese architecture which was built in 1770 by PB IX has undergone some changes but the  core building is relatively unchanged. There are two kinds of joglo, namely, prawitan and limasan. The front building is known as Pendapa and the rear building is called Dalem Probosuyasa.  Dalem is a place where the King takes a rest and meditates. It is also the place of heirloom and of equipments for ritual. Pendhapa Sasana Sewaka has the function as pasewakan, that is, the  place where patih (chief minister to a king) appears before the king and where government officials, the relatives of the king hold a meeting and other purposes which have something to do with the  court. Pendhapa Sasana Sewaka is also the place where Bedhaya Ketawang dance which symbolizes the meeting between the king and Kencana Asri, the queen of south sea, takes place. Pendhapa Sasana Sewaka is very meaningful for the life of the court because every business that has something to do with the legitimacy of the king, government, culture and rituals is held in it. Pendhapa Sasana Sewaka faces to the east and in front of it is a large yard having sand in it. Pendapa has floor made of white marble. It has four carved pillars and between the two pillars in the west is the royal throne placed. The king as the symbol of Wisnu who wants to be responsible for the peace of the universe sits on the throne at anniversary day of the coronation and on important days. At the certain places of the ceiling hang some decorative chandeliers, making the pendapa more noble, luxurious, authoritative, and haughty. All of the forms of the buildings and activities are full of symbolical and mystic values and meanings.Key words: sasana Sewaka, mythology, symbolic, and meaning.